Cranial autonomic symptoms and response to monoclonal antibodies targeting the Calcitonin gene-related peptide pathway: A real-world study - De Matteis, Eleonora; Caponnetto, Valeria; Casalena, Alfonsina; Frattale, Ilaria; Gabriele, Amleto; Affaitati, Giannapia; Giamberardino, Maria Adele; Maddestra, Maurizio; Viola, Stefano; Pistoia, Francesca; Sacco, Simona; Ornello, Raffaele (Frontiers in Neurology, 2022)
Objective Cranial autonomic symptoms (CAS), including conjunctival injection, tearing, nasal congestion or rhinorrhea, eyelid edema, miosis or ptosis, and forehead or facial sweating ipsilateral to headache, are often reported by patients with migraine during headache attacks. CAS is a consequence of the activation of the trigeminovascular system, which is the target of monoclonal antibodies acting on the CGRP pathway. Therefore, we hypothesized that patients with CAS might have higher trigeminovascular activation than those without CAS leading to a better response to anti-CGRP treatments. Methods We performed a prospective analysis including patients with episodic or chronic migraine treated with anti-CGRP monoclonal antibodies (i.e., erenumab, fremanezumab, and galcanezumab) between 2019 and 2021. The observation period included a 12-week baseline before treatment with anti-CGRP antibodies and a 12-week treatment follow-up. We evaluated the prevalence of CAS in our cohort and compared disease characteristics and treatment response (i.e., 12-week monthly headache days and 0–29, 30–49, 50–74, 75–99, and 100% monthly headache days reduction from baseline) among patients with and without CAS using the χ2 test, Kruskal–Wallis test, and Mann–Whitney U-test. Results Out of 136 patients, 88 (65%) had CAS. Both patients with and without CAS reported a significant decrease in monthly headache days from baseline. During the 12-week follow-up, the median difference in monthly headache days from baseline was higher in patients with CAS (-10, IQR−15 to−6) than in those without CAS (6, IQR 12 to 3; P = 0.009). However, the proportions of patients with 0 to 29, 30 to 49, 50 to 74, 75 to 99, and 100% response rates did not differ between the two groups. Conclusions In our cohort, the presence of CAS was associated with a greater response to monoclonal antibodies targeting the CGRP pathway. CAS could be a clinical marker of trigeminovascular activation and thus be related to a better response to CGRP treatments.